Sintesis Aluminium Formate-MOF dari Limbah Kaleng sebagai Material Penangkap Karbon Menggunakan Metode Solvotermal - Parmadi, Faris Achmad; Nurjannah, Nikmah; Ramadhani, Muhammad Ardycha Yudha; Wulandari, Amalia; Anjasmoro; Arifin, Zainal (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2024)
This research aims to synthesize and characterize aluminum formate-metal organic framework (ALF-MOF) from beverage can waste using solvothermal method. The solvothermal method was chosen due to its ability to produce materials with controlled structures and superior properties. This research also uses a Central Composite Design (CCD) experimental design to optimize the synthesis conditions. The ALF-MOF synthesis process was carried out by mixing Al(OH)3 powder obtained from the extraction of aluminum in beverage can waste and HCOOH in DMF. The mixture was stirred and heated in an autoclave reactor at Al/HCOOH mole ratios (1:3, 1:5, and 1:7) and reaction times (1, 2, and 3 hours). Furthermore, the products were characterized using FTIR, XRD, SEM, and BET. Based on the results, it is known that the optimum synthesis conditions were achieved at the Al/HCOOH mole ratio and reaction time of 1:3.729 and 2.874 hours, respectively, with an ALF-MOF yield value of 87.71%. Characterization results showed the presence of COO groups and Al-O-Al groups. The ALF-MOF product also has an average particle diameter of 23.57 nm with a %crystallinity of 51.30% and a surface area of 128.507 m2/gram.